2011
DOI: 10.1128/aem.06174-11
|View full text |Cite
|
Sign up to set email alerts
|

Examination of the Seasonal Dynamics of the Toxic Dinoflagellate Alexandrium catenella at Redondo Beach, California, by Quantitative PCR

Abstract: The presence of neurotoxic species within the genus Alexandrium along the U.S. coastline has raised concern of potential poisoning through the consumption of contaminated seafood. Paralytic shellfish toxins (PSTs) detected in shellfish provide evidence that these harmful events have increased in frequency and severity along the California coast during the past 25 years, but the timing and location of these occurrences have been highly variable. We conducted a 4-year survey in King Harbor, CA, to investigate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(28 citation statements)
references
References 64 publications
1
27
0
Order By: Relevance
“…For each depth, two 400 mL volumes were filtered through glass fiber filter membranes. The filters were processed as crude lysates, as in Garneau et al (2011), and filtered through a 0.22 mm, low-binding cellulose acetate syringe-tip filters to efficiently remove cellular debris and filter remnants. The P. rubescens filaments were quantified following the qPCR TaqMan assay on the 16S ribosomal deoxyribonucleic acid (rDNA) gene developed by Ostermaier and Kurmayer (2009).…”
Section: Methodsmentioning
confidence: 99%
“…For each depth, two 400 mL volumes were filtered through glass fiber filter membranes. The filters were processed as crude lysates, as in Garneau et al (2011), and filtered through a 0.22 mm, low-binding cellulose acetate syringe-tip filters to efficiently remove cellular debris and filter remnants. The P. rubescens filaments were quantified following the qPCR TaqMan assay on the 16S ribosomal deoxyribonucleic acid (rDNA) gene developed by Ostermaier and Kurmayer (2009).…”
Section: Methodsmentioning
confidence: 99%
“…Garneau et al (2011) reported a rather weak correlation (r s ¼ 0.54, P < 0.0001) in a study on PSPtoxigenic A. catenella (Group I) from California, based upon a similar number of samples (n ¼ 91). In Garneau et al's study, the highest peak in cell numbers did not match the highest amount of measured PSP toxin in the samples and sometimes the Alexandrium cells detected and the toxin concentration did not match at all.…”
Section: Tests Of the New Qpcr Assaymentioning
confidence: 95%
“…There has been extensive application of various qPCR methods to determine changes in phytoplankton communities (Handy et al, 2006(Handy et al, , 2008 and they have also been used successfully for the detection of harmful microalgae (e.g. Galluzzi et al, 2004;Dyhrman et al, 2006;Touzet et al, 2009;Garneau et al, 2011), including cysts of Alexandrium spp. (Kamikawa et al, 2005(Kamikawa et al, , 2007, in laboratory cultures and field samples.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The expanse of this real-time PCR research has been significant, with a number of methods being reported for dinoflagellates, diatoms and members of Raphidophyceae, Haptophyceae, Pelagophyceae and Cyanophyceae [61]. Applications directed at the detection of Alexandrium species such as A. catenella [62][63][64][65][66], A. minutum [26,67], A. fundyense [68,69], A. taylori [64] and A. tamarense [62,63,70] have been thoroughly reported. Similarly, real-time PCR methods were developed for the dinoflagellate species Dinophysis acuta and D. acuminata [71].…”
Section: Real-time Pcr Applicationsmentioning
confidence: 99%